Use of thermo‐coagulation as an alternative treatment modality in a 'screen‐and‐treat' programme of cervical screening in rural Malawi. Issue 4 (4th May 2016) - Campbell, Christine; Kafwafwa, Savel; Brown, Hilary; Walker, Graeme; Madetsa, Belito; Deeny, Miriam; Kabota, Beatrice; Morton, David; Ter Haar, Reynier; Grant, Liz; Cubie, Heather A.
Abstract : The incidence of cervical cancer in Malawi is the highest in the world and projected to increase in the absence of interventions. Although government policy supports screening using visual inspection with acetic acid (VIA), screening provision is limited due to lack of infrastructure, trained personnel, and the cost and availability of gas for cryotherapy. Recently, thermo‐coagulation has been acknowledged as a safe and acceptable procedure suitable for low‐resource settings. We introduced thermo‐coagulation for treatment of VIA‐positive lesions as an alternative to cryotherapy within a cervical screening service based on VIA, coupled with appropriate, sustainable pathways of care for women with high‐grade lesions and cancers. Detailed planning was undertaken for VIA clinics, and approvals were obtained from the Ministry of Health, Regional and Village Chiefs. Educational resources were developed. Thermo‐coagulators were introduced into hospital and health centre settings, with theoretical and practical training in safe use and maintenance of equipment. A total of 7, 088 previously unscreened women attended VIA clinics between October 2013 and March 2015. Screening clinics were held daily in the hospital and weekly in the health centres. Overall, VIA positivity was 6.1%. Almost 90% received same day treatment in the hospital setting, and 3‐ to 6‐month cure rates of more than 90% are observed. Thermo‐coagulation proved feasible and acceptable in this setting. Effective implementation requires comprehensive training and provider support, ongoing competency assessment, quality assurance and improvement audit. Thermo‐coagulation offers an effective alternative to cryotherapy and encouraged VIA screening of many more women. Abstract : What's new? Malawi has the highest incidence rates for cervical cancer worldwide, and a "screen‐and‐treat" program is in place to identify and treat precancerous lesions. Conventional cryotherapy is challenging as gas supply is inconsistent, cylinders are difficult to transport and running costs are high. Here, the authors introduce thermo‐coagulation as a treatment alternative, which proved feasible and acceptable in this resource‐poor setting and could increase the number of women receiving timely treatment for precancerous lesions in low‐ and middle‐income countries.